2017
DOI: 10.1111/lre.12185
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of climate change and stratification in Lake Kariba (Zambia–Zimbabwe)

Abstract: Lake Kariba is a monomictic reservoir, isothermal in winter (June–August), and stratified for the rest of the year. Its temperature has increased since the 1990s, with some researchers suggesting it now has a stronger and more stable thermocline as a result. It was also claimed that the depth of the epilimnion had decreased, and nutrient depletion has led to a decrease in the depth of the euphotic zone, algal biomass and primary productivity. A re‐analysis of the data suggests this view is incorrect. The epili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A weak thermocline has been detected in studies by Mahere et al [85] and Marshall [86] in Lake Kariba, which has been acknowledged to be experiencing warming temperatures. On the other hand, Mahere et al [85] and Marshall [86] claimed that the perceived warming temperatures of Lake Kariba led to an increase in algal biomass and primary productivity. Therefore, the thermal stratification of inland freshwater bodies has and will continue to affect fish production, either by increasing or decreasing fish productivity.…”
Section: Thermal Stratificationmentioning
confidence: 93%
See 1 more Smart Citation
“…A weak thermocline has been detected in studies by Mahere et al [85] and Marshall [86] in Lake Kariba, which has been acknowledged to be experiencing warming temperatures. On the other hand, Mahere et al [85] and Marshall [86] claimed that the perceived warming temperatures of Lake Kariba led to an increase in algal biomass and primary productivity. Therefore, the thermal stratification of inland freshwater bodies has and will continue to affect fish production, either by increasing or decreasing fish productivity.…”
Section: Thermal Stratificationmentioning
confidence: 93%
“…Contrary to Vincent [82] and Ndebele-Murisa et al [18], who state that warming temperatures promote stratification, Mahere et al [85] and Marshall [86] claimed that warming temperature weakens the thermocline (less pronounced stratification). A weak thermocline has been detected in studies by Mahere et al [85] and Marshall [86] in Lake Kariba, which has been acknowledged to be experiencing warming temperatures. On the other hand, Mahere et al [85] and Marshall [86] claimed that the perceived warming temperatures of Lake Kariba led to an increase in algal biomass and primary productivity.…”
Section: Thermal Stratificationmentioning
confidence: 94%
“…The lake has a surface area of 4 364 km 2 at the normal operation level of 484 m a.s.l, a length of 276 km, an average width of 19 km, and an average depth of 29 m [ 24 ]. The lake is warm, nutrient-poor, and monomictic [ 25 , 26 ]. It is divided into five major hydrological basins: Mlibizi (Basin 1), Binga (Basin 2), Sengwa (Basin 3), Bumi (Basin 4), and Sanyati (Basin 5).…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that climatic variability was contributing to the declines in fish catches and changes in species composition. Marshall (2017) noted that the thermocline in the Lake has weakened, with much smaller density and thermal gradients compared to the 1980s. Mhlanga et al(2018) found that under climate change scenarios RCP 8.5 and 6.0 areas suitable for dairy farming will decrease by 25.4% and 2.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%